Association of antipsychotic use with breast cancer: a systematic review and meta-analysis of observational studies with over 2 million individuals. (5th September 2022) - Leung, Janice Ching Nam; Ng, Dora Wai Yee; Chu, Rachel Yui Ki; Chan, Edward Wai Wa; Huang, Lei; Lum, Dawn Hei; Chan, Esther Wai Yin; Smith, Daniel J.; Wong, Ian Chi Kei; Lai, Francisco Tsz Tsun
Abstract: Aims: Despite reports of an elevated risk of breast cancer associated with antipsychotic use in women, existing evidence remains inconclusive. We aimed to examine existing observational data in the literature and determine this hypothesised association. Methods: We searched Embase, PubMed and Web of Science™ databases on 27 January 2022 for articles reporting relevant cohort or case-control studies published since inception, supplemented with hand searches of the reference lists of the included articles. Quality of studies was assessed using the Newcastle-Ottawa Scale. We generated the pooled odds ratio (OR) and pooled hazard ratio (HR) using a random-effects model to quantify the association. This study was registered with PROSPERO (CRD42022307913). Results: Nine observational studies, including five cohort and four case-control studies, were eventually included for review ( N = 2 031 380) and seven for meta-analysis ( N = 1 557 013). All included studies were rated as high-quality (seven to nine stars). Six studies reported a significant association of antipsychotic use with breast cancer, and a stronger association was reported when a greater extent of antipsychotic use, e.g. longer duration, was operationalised as the exposure. Pooled estimates of HRs extracted from cohort studies and ORs from case-control studies were 1.39 [95% confidence interval (CI) 1.11–1.73] and 1.37 (95% CI 0.90–2.09), suggesting a moderate association of antipsychotic use with breast cancer. Conclusions: Antipsychotic use is moderately associated with breast cancer, possibly mediated by prolactin-elevating properties of certain medications. This risk should be weighed against the potential treatment effects for a balanced prescription decision.